Gospels and gospel traditions in the second century : experiments in reception - Schröter, Jens, 1961-; Nicklas, Tobias, 1967-; Verheyden, Joseph, 1957-; Simunovic, Katharina; Leuven Centre for the Study of the Gospels. International Symposium 2016 : Louvain, Belgium) (Berlin ; Boston : De Gruyter, 2019)
"The second century CE has often been described as a kind of dark period with regard to our knowledge of how the earliest Christian writings (the gospels and Paul's letters) were transmitted and gradually came to be accepted as authoritative and then, later on, as "canonical". At the same time a number of other Christian texts, of various genres, saw the light. Some of these seem to be familiar with the gospels, or perhaps rather with gospel traditions identical or similar to those that found their way into the NT gospels. The volume focuses on representative texts and authors of the time in order to see how they have struggled to find a way to work with the NT gospels and/or the traditions behind these, while at the same time giving a place also to other extra-canonical traditions. It studies in a comparative way the reception of identifiably "canonical" and of extra-canonical traditions in the second century. It aims at discovering patterns or strategies of reception within the at first sight often rather chaotic way some of these ancient authors have cited or used these traditions. And it will look for explanations of why it took such a while before authors got used to cite gospel texts (more or less) accurately."--
Greek New Testament papyri and their text in the second-third centuries / James Keith Elliott -- Replaying Jesus' sayings in the "Agrapha": Reflections on the Neu-Inszenierung of Jesus' traditions in the second century between 2 Clement and Clement of Alexandria / Giovanni Bazzana -- Conflated citations of the Synoptic Gospels: the beginnings of Christian doxographic tradition? / John Kloppenborg -- Ignatius and the Gospels / Paul Foster -- On the miracle catena in Epistula Apostolorum 4-5 / Francis Watson -- Marcion's Gospel and the Synoptics: proposals and problems / Daniel A. Smith -- "Worte Gottes, verkündigt von den Aposteln": Evangelienzitate bei Justin / Katharina Greschat -- Thomas unter den Evangelisten: zum Ort des Thomasevangeliums in der frühchristlichen Literatur / Jens Schröter -- Irenäus und die Evangelien: literarische Rezeption "des Herrn" und Anschluss an eine Vierertradition / Bernhard Mutschler -- "He who has seen me, has seen the Father" : the Gospel of Philip's mystagogical reception of the Gospel of John / Hugo Lundhaug -- Principles of Gnostic exegesis / Christopher M. Tuckett -- Zwischen Redaktion und "Neuinszenierung": vom Umgang erzählender Evangelien des 2. Jahrhunderts mit ihren Vorlagen / Tobias Nicklas.
Online resource; title from PDF title page (EBSCO, viewed April 16, 2019)
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Bible. -- Criticism, Redaction -- Congresses; Bible. -- Criticism, interpretation, etc. -- History -- Early church, ca. 30-600 -- Congresses; Bible. -- Criticism, Redaction -- Congresses; Bible; Bible; Apocryphal Gospels -- Congresses; Gnostic literature -- Relation to the New Testament -- Congresses; Évangiles apocryphes -- Congrès.; Littérature gnostique -- Relation avec le Nouveau Testament -- Congrès.; RELIGION -- Biblical Studies -- Jesus, the Gospels & Acts; RELIGION -- Biblical Studies -- New Testament; Apocryphal Gospels; Gnostic literature -- Relation to the New Testament; 30-600; Conference papers and proceedings; Criticism, interpretation, etc; History